Heterogeneity of soil surface ammonium concentration and other characteristics, related to plant specific variability in a Mediterranean-type ecosystem - Cruz, Cristina (2011)
ACESSO via B-on: http://dx.doi.org/10.1016/j.envpol.2007.12.007